1978
DOI: 10.1243/emed_jour_1978_007_061_02
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Strength of Cobalt-Base Alloys with High Corrosion Resistance for Artificial Hip Joints

Abstract: Loosening of the anchorage in the bone is a problem in hip-joint arthroplasty which up to now has not been entirely solved. In the loosened condition, anchorage stems of artificial joints are subject to alternating overload which causes rupture if the fatigue strength is exceeded by the stress amplitude. At Sulzer a hip-joint anchorage stem made from wrought CoNiCrMo alloy Protasul-10 has been developed which has substantially higher fatigue strength than stems made from stainless steel of grade AISI-316L or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1982
1982
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Surprisingly, it has also been reported that strength was not markedly enhanced by unidirectional solidification. 2 The results contradict not only the reported improvement of fatigue life using unidirectional solidification but also, for example, the investigation of VerSnyder,3 who observed the improvement of high-temperature fatigue life of turbine blades using unidirectional solidification.…”
Section: Fatigue Testmentioning
confidence: 69%
“…Surprisingly, it has also been reported that strength was not markedly enhanced by unidirectional solidification. 2 The results contradict not only the reported improvement of fatigue life using unidirectional solidification but also, for example, the investigation of VerSnyder,3 who observed the improvement of high-temperature fatigue life of turbine blades using unidirectional solidification.…”
Section: Fatigue Testmentioning
confidence: 69%
“…The cast CoCr alloy used in the 1950s for the Austin Moore prosthesis had an endurance limit in the range of 175-280 MPa for zero-tension loading (16,19,24). Defects in the cast metal could further decrease fatigue strength (24,27).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of cement fracture was assessed against fatigue. Cement cracks where found to propagate in mode I (opening mode) in stable implants with no evidence of ongoing adverse biological processes; this mode is typically related to tensile stresses [42]. The highest tensile strains induced in the cement by common activities of daily living were compared with the endurance limit for acrylic bone cement to verify that non-relevant damage accumulation was possible.…”
Section: Aseptic Looseningmentioning
confidence: 99%